NLRP3 Inflammasome Promotes the Progression of Acute Myeloid Leukemia via IL-1β Pathway - Zhong, Chaoqin; Wang, Ruiqing; Hua, Mingqiang; Zhang, Chen; Han, Fengjiao; Xu, Miao; Yang, Xinyu; Li, Guosheng; Hu, Xiang; Sun, Tao; Ji, Chunyan; Ma, Daoxin (Frontiers in Immunology, 2021)
NLRP3 inflammasome has been reported to be associated with the pathogenesis of multiple solid tumors. However, the role of NLRP3 inﬂammasome in acute myeloid leukemia (AML) remains unclear. We showed that NLRP3 inflammasome is over-expressed and highly activated in AML bone marrow leukemia cells, which is correlated with poor prognosis. The activation of NLRP3 inflammasome in AML cells promotes leukemia cells proliferation, inhibits apoptosis and increases resistance to chemotherapy, while inactivation of NLRP3 by caspase-1 or NF-κB inhibitor shows leukemia-suppressing effects. Bayesian networks analysis and cell co-culture tests further suggests that NLRP3 inflammasome acts through IL-1β but not IL-18 in AML. Knocking down endogenous IL-1β or anti-IL-1β antibody inhibits leukemia cells whereas IL-1β cytokine enhances leukemia proliferation. In AML murine model, up-regulation of NLRP3 increases the leukemia burden in bone marrow, spleen and liver, and shortens the survival time; furthermore, knocking out NLRP3 inhibits leukemia progression. Collectively, all these evidences demonstrated that NLRP3 inflammasome promotes AML progression in an IL-1β dependent manner, and targeting NLRP3 inflammasome may provide a novel therapeutic option for AML.